Banking Dynamics and Economic Growth in India : Unveiling the Interplay of Key Performance Indicators - Naveenan, R. V.; Viswanathan, T. (Indian Journal of Finance, 2025)
Purpose : This study aimed to analyze the influence of bank performance on economic growth. We proposed a framework of banking variables to gain a holistic picture. Design/Methodology/Approach : To identify the causal relationship, we ran cointegration tests and vector autoregression (VAR). In addition, we used the impulse response function test. This helped in analyzing the response of GDP growth to banking shocks. Findings : We identified that banking variables like domestic credit (DC), return on equity, and capital adequacy ratio can stimulate economic growth. Long-term and short-term influence of banking performance on economic growth. Improved performance of banks can translate to economic growth. Our results also indicated that well-capitalized banking, high return on equity, and increased credit access were critical drivers of GDP growth. Practical Implications : This research offered important insights into the role of banking performance in influencing economic growth. We recommended that policymakers implement measures to improve capital adequacy, enhance profitability, and increase credit flow for sustained economic success and development. Originality/Value : This study added to existing research by examining how banking performance influenced economic growth in a developing context. Unlike prior studies that focused mainly on advanced economies, our analysis centered on India, offering evidence from an emerging financial system and providing context-specific insights.